Propensity-matched comparison between minimally invasive and conventional sternotomy in aortic valve resuspension. (16th January 2018) - Monsefi, Nadejda; Risteski, Petar; Miskovic, Aleksandra; Zierer, Andreas; Moritz, Anton
Abstract: OBJECTIVES: The aim of the study was to compare the results of David procedure through conventional or minimally invasive approach. METHODS: A propensity-matched comparison in patients undergoing a minimally invasive (partial upper sternotomy, n  = 103) or complete sternotomy ( n  = 103) David procedure from 1991 to 2016 was performed. Patients were 57 ± 14 years old on average in both groups. The David technique was modified by generating a neosinus ( P  < 0.01) in 99 (96%) patients (minimally invasive group) and in 42 (41%) patients (complete sternotomy group), respectively. The average follow-up time was 3 ± 2 years (minimally invasive group) and 8 ± 4 years (complete sternotomy group). RESULTS: There was only 1 in-hospital death (in the full sternotomy group, P  = 0.5). The applied quantity of packed red blood cells (pRBC) was significantly higher in the complete sternotomy group (3.4 ± 4 vs 1 ± 0.5, P  < 0.01). There were no late deaths in the minimally invasive group but 14 died during a longer follow-up period in the full sternotomy group ( P  < 0.01). Freedom from reoperation or aortic valve insufficiency ≥2° was 95% vs 93% (minimally invasive versus complete sternotomy group) at 5 years and 95% vs 79% at 10 years ( P  < 0.01). CONCLUSIONS: The minimally invasive aortic valve reimplantation procedure for selected patients with aortic root aneurysm and aortic valve incompetence is a durable procedure with minor valve-related morbidity and mortality at the mid-term follow-up. The intra- and perioperative application of pRBC was significantly lower in the minimally invasive group. However, comparison of long-term follow-up data in both groups is necessary to evaluate valve function.